(untitled) (International Forum Journal, 2007)
This paper examines the writings of Ellen White for the presence and application of several key adult education principles as identified by Malcolm Knowles. The practical application of these principles is then examined in the teaching of college English as a second language and compulsory general education Bible classes. These principles can also be applied to other areas, and their implementation will make for better teachers who will inte-grate their faith in their content areas, and may provide clues for the improvement of strategies for communicating the gospel to adults.